Fast-growing Companies: Economic Growth Sources in Russian Agriculture - Oleg I. DRANKO; Marina M. DVORYASHINA (Communications of International Proceedings, 2021)
We have investigated the revenue growth impact on the company’s key performance indicators: profitability and business value. The fast-growing companies (FGC) segment of the Russian economy’s agricultural sector is highlighted to study the micro-level economic growth determinants. The analysis of FGC activities was carried out using open data sources: Rosstat, FTS of Russia, financial statements of companies. BI technologies were used to process the data. The total revenue (34 companies) of fast-growing agricultural companies in 2019 amounted to 3.8% of the Russian agricultural complex’s revenue. The financial condition of fast-growing agricultural companies has improved dramatically in 5 years. The uneven growth of the FGC and the high dynamics of the FGC, in general, indicate the high turbulence of the Russian agricultural markets. The regional distribution over the territory of Russia is close to uniform. This is consistent with the goals of maximizing business value on the top management and is manifested in the capture of regional (interregional) agricultural markets by such companies.
Keywords: Fast-Growing Companies; Economic Growth Sources; Multilevel Analysis Model; Targeted Tools of Support